Understanding functional dyspepsia and its subtypes and the role of prokinetics in its management: a cross-sectional clinician-based survey - Mukewar, Shrikant; Pratap, Nitesh; Jain, Samit (International Journal of Advances in Medicine, 2023)
Background: This survey evaluated opinions of consulting physicians or gastroenterologists on functional dyspepsia (FD) in the Indian population and the management of FD with prokinetics, especially itopride. Methods: A total of 243 clinicians involved in the clinical practice of FD were invited to complete an internet-based, structured survey questionnaire. Questionnaire comprised 29 questions on the diagnosis and treatment options for FD. Results: Majority of the clinicians opined that females were more affected by FD than males in both hospital-based (53.4%) and community-based (56.6%) practices. As per 33.3% of clinicians each, the age group of 21-40 years and 41-60 years were the two most commonly affected groups. FD symptoms were present for >6 months before patients seek consultation as reported by 62.6% of the clinicians. The participating clinicians preferred using detailed patient history (77.7%) and ROME IV criteria (71.1%) for diagnosing FD. Prokinetics were regarded as the therapy of choice primarily because of their efficacy in reducing FD symptoms. Among all prokinetics used, itopride was most preferred for postprandial distress syndrome (64.2% clinicians) and for epigastric pain syndrome in combination with PPIs (66.7% clinicians). Itopride was reported by 93.6% clinicians to be well tolerated, with the leading advantage being absence of extrapyramidal or cardiac side effects according to 40% of clinicians. Conclusions: The clinicians considered itopride to be most preferred to reduce FD symptoms and to be well-tolerated when taken alone or in combination with PPIs.